EFFECTIVENESS OF USING ELEMENTS OF NANOTECHNOLOGY IN CONSTRUCTION MATERIALS SCIENCE - Bakhodir Rizayev1, Islombek Akhmedov1, Shavkat Yusupov 1, Isroiljon Umarov1, Aleksandir Kazadayev1, Farrukh Dadakhanov1 (Journals Park Publishing, 2022)
Nanotechnology is an applied science that deals with the creation of fundamentally new instruments and materials at extremely small sizes, and studies the properties of various substances at the atomic and molecular level.